The distinctive molecular, pathological and clinical characteristics of BRAF-mutant colorectal tumors. (November 2015) - Scartozzi, Mario; Giampieri, Riccardo; Aprile, Giuseppe; Iacono, Donatella; Santini, Daniele; dell'Aquila, Emanuela; Silvestris, Nicola; Gnoni, Antonio; Bonotto, Marta; Puzzoni, Marco; Demurtas, Laura; Cascinu, Stefano
<x xml:space="preserve">Abstract</x> Several clinical series have demonstrated a notably low overall survival for colorectal cancer patients diagnosed with a BRAF-mutant tumor. A potentially interesting predictive role has also been suggested for BRAF-mutant colorectal cancer receiving anti-EGFR monoclonal antibodies. Although a global consensus exists in indicating BRAF as a prognostic factor with a possible predictive activity, the clinical use of BRAF mutational status in colorectal tumors is still controversial. This article reviews the current knowledge on the use and implications of BRAF mutational status in colorectal tumors, in order to define its present role in the clinical practice. Also suggested are possible treatment strategies in this prognostically challenging group of patients. Finally, a comprehensive outlook on future developments for specifically directed anti-BRAF therapy is illustrated.